Uso de Panax ginseng e Angelica keiskei para potencialização do efeito vasodilatador induzido pela fotobiomodulação (660 nm) - Moraes, Luis Henrique Oliveira de (Universidade Federal de São Carlos, 2025)
Endothelial dysfunction is a hallmark of renovascular hypertension and a critical barrier to effective vascular therapies. This study explored the synergistic potential of combining phytotherapy with photobiomodulation (PBM) to restore endothelial function through nitric oxide (NO)-mediated mechanisms. Using the 2-kidney-1-clip (2K1C) hypertensive model in rats, as well as in vitro assays with human endothelial cells and isolated vascular preparations, we evaluated the effects of a standardized combination of Panax ginseng and Angelica keiskei—plants known for their antioxidant and vasorelaxant properties. Intermittent administration of the extract improved endothelium-dependent vasodilation and enhanced NO sensitivity, despite modest effects on blood pressure. When paired with PBM (660 nm), the herbal treatment significantly potentiated vasodilatory responses in aortic rings, an effect abolished by endothelium removal or NO pathway inhibition, suggesting eNOS dependency. Inhibition of eNOS via L-NAME blunted these effects but revealed partial endothelial compensation in acetylcholine responses. Cellular assays confirmed increased intracellular NO and reduced superoxide production, indicating redox balance restoration. Together, these findings underscore a mechanistic interplay between phytotherapy and PBM, driven by eNOS activation and oxidative stress modulation, offering a promising non-pharmacological strategy to counteract endothelial dysfunction in hypertension.
Use of Panax ginseng and Angelica keiskei to enhance the vasodilatory effect induced by photobiomodulation (660 nm)
Keywords: Fotobiomodulação; Fitoterapia; Hipertensão; Óxido nítrico; Disfunção endotelial; CIENCIAS BIOLOGICAS::FISIOLOGIA; 3. Saúde e Bem-Estar